Patterns of traumatic brain injury and six-month neuropsychological outcomes in Uganda - Bangirana, Paul (BMC Neurol, 2019)
BACKGROUND: Traumatic brain injuries in Uganda are on the increase, however little is known about the neuropsychological outcomes in survivors. This study characterized patients with traumatic brain injury (TBI) and the associated six-month neuropsychological outcomes in a Ugandan tertiary hospital. METHODS: Patients admitted at Mulago Hospital with head injury from November 2015 to April 2016 were prospectively enrolled during admission and followed up at six months after discharge to assess cognition, posttraumatic stress symptoms (PTSS), depression symptoms and physical disability. The outcomes were compared to a non-head-injury group recruited from among the caretakers, siblings and neighbours of the patients with age and sex entered as covariates. RESULTS: One hundred and seventy-one patients and 145 non-head injury participants were enrolled. The age range for the whole sample was 1 to 69 years with the non-head injury group being older (mean age (SD) 33.34 (13.35) vs 29.34 (14.13) years of age, p = 0.01). Overall, motorcycle crashes (36/171, 38.6%) and being hit by an object (58/171, 33.9%) were the leading causes of TBI. Head injury from falls occurred more frequently in children < 18 years (13.8% vs 2.8%, p = 0.03). In adults 18 years and older, patients had higher rates of neurocognitive impairment (28.4% vs 6.6%, p < 0.0001), PTSS (43.9% vs 7.9%, p < 0.0001), depression symptoms (55.4% vs 10%, p < 0.0001) and physical disability (7.2% vs 0%, p = 0.002). Lower Glasgow Coma Score (GCS) on admission was associated with neurocognitive impairment (11.6 vs 13.1, p = 0.04) and physical disability (10 vs 12.9, p = 0.01) six months later. CONCLUSION: This first such study in the East-African region shows that depth of coma on admission in TBI is associated with neurocognitive impairment and physical disability.